Hubungan Tingkat pendidikan dan Pendapatan Keluarga dengan Kesiapsiagaan Ibu Hamil dan Keluarga Menghadapi Erupsi Gunung Agung - Dian Octaviana Rasta Efendi; Nengah Runiari; I Dewa Made Ruspawan (Jurnal Gema Keperawatan, 2022)
The lack of preparedness of pregnant women and their families in dealing with disasters is one of the causes of delays in making decisions when facing disasters, especially the eruption of Mount Agung. Factors that affect preparedness include education levels and family income. This study aims to determine the association between education level and family income with the preparedness of pregnant women and families to face the eruption of Mount Agung in the working area of the Selat Public Health Center. The research method in this study was quantitative with a correlational analytical design using a cross-sectional approach. The sampling technique used purposive sampling of as many as 64 people. Collecting data using primary data with a questionnaire sheet. The results showed that most of the pregnant women with a junior high school education level, namely 21 people (32.8%), the family income of pregnant women was almost balanced with an income of IDR 2,500,000, i.e. as many as 35 families (54.7%), and Most of the preparedness of pregnant women to face the eruption of Mount Agung was in the moderate category, namely 24 people (37.5%). The results of the Spearman test show that the level of education (p value = 0.000) (α = 0.05) and family income (p value = 0.058) ( = 0.05), it can be concluded that there is a significant association between the level of education and the preparedness of pregnant women facing the eruption of Mount Agung, but there is no significant association between family income and the preparedness of pregnant women facing the eruption of Mount Agung in the Working Area of the Selat Public Health Center.